Use substitution and substitute y into the other equation. One of the equations already gives you y in terms of x, so use that and substitute it into the other equation. y = 3x - 4
Plug into the other equation: -3y = -9x + 12
-3(3x-4) = -9x + 12
-9x + 12 = -9x + 12
This is an identity. So that means that any value of x makes this equation true. So B.
Answer:
4
Step-by-step explanation:
7+(-14)+(-6)+13+4
7+(-20)+13+4
(-13)+13+4
0+4
4
Answer:
C. 2 is less than or equal to x
Step-by-step explanation:
E d g e n u i t y 2020
Answer:
B
Step-by-step explanation:
B
Answer:
36
Step-by-step explanation:
![\frac{0.25}{0.75} =\frac{12}{x} \\](https://tex.z-dn.net/?f=%5Cfrac%7B0.25%7D%7B0.75%7D%20%3D%5Cfrac%7B12%7D%7Bx%7D%20%5C%5C)
![0.75 *12=9](https://tex.z-dn.net/?f=0.75%20%2A12%3D9)
![\frac{9}{0.25} =36](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B0.25%7D%20%3D36)